Effect of Cow\'s-milk-free diet on chronic constipation in children; A randomized clinical trial - Atena Mohammadi Bourkheili; Sanaz Mehrabani; Mohammadreza Esmaelidooki; Mahmood Haji Ahmadi; Leila Moslemi (Babol University of Medical Sciences, 2021)
Background: Cow's milk intolerance can lead to chronic constipation in children. The present study seeks to determine the effect of cow's milk-free diet (CMFD) on chronic constipation in children who are not responding to laxatives. Methods: Seventy children suffering from chronic constipation (described as the Rome III criteria) were enrolled in an open-label randomized clinical study. Each group included 35 children aged 4-14 years treated with laxatives for at least three months with no improvements. The intervention group received CMFD plus calcium supplements for four weeks and the control group did not have any restrictions in consuming cow's milk and dairy products. Also, both groups received polyethylene glycol (PEG; 1 gr/kg/day) and high-fiber foods (at least 10 gr/day) for four weeks. Responsiveness was described as a reduction in symptoms and signs according to the Rome III criteria after four weeks. Results: After four weeks, 25 (71.4%) children in the CMFD group responded to the treatment compared to four (11.4%) children in the control group (P<0.001). Significant differences were found between the CMFD and control groups in terms of the seven Rome III criteria post-intervention; history of large stools (25% vs. 53.6%), large fecal mass in the rectum during examination (17.1% vs. 50%), history of painful defecation (18.2% vs. 55.6%), history of retentive posturing (10% vs. 46%), ≥1 episode/week of incontinence (25 % vs. 50%, P=0.001), ≤ 2 defecations/week (17.4% vs. 52.3%) and history of thick stool with toilet obstruction (22.2% vs. 52.3%) Conclusion: This study showed that children with functional constipation with no response to laxatives could benefit from a cow's milk-free and dairy-free diet.